Distribution and Diversity of Sand Fly Species (Diptera: Psychodidae, Phlebotominae) in Two Geoclimatic Zones of Chad - Israël, Demba Kodindo; Coulibaly, Cheick Amadou; Sissoko, Ibrahim Moussa; Traoré, Bourama; Wilke, André B. B.; Beier, John C.; Muller, Gunter C.; Doumbia, Seydou (Frontiers in Tropical Diseases, 2022)
Leishmaniasis transmitted by sandflies is an important vector-borne disease. In Chad, information on sandflies is outdated, and so this study was designed to update the sandfly fauna. Sandflies were collected in five health districts representing two geoclimatic zones using sticky traps and pyrethrum sprays in indoor and peridomestic habitats between September 2019 and December 2020. All collected sandfly specimens were identified based on species-level morphological characters. A total of 2,015 specimens belonging to 13 species of sandflies (one Phlebotomus and twelve Sergentomyia) were collected and identified. The vector of human cutaneous leishmaniasis, Phlebotomus duboscqi, represents 0.65% of all collected sandflies and is the only representative of the Phlebotomus genus to be collected predominantly inside human dwellings. Phlebotomus orientalis, the vector of visceral leishmaniasis previously collected in Chad in 1976 was not found in this study. Sergentomyia clydei, Sergentomyia schwetzi, Sergentomyia antennata and Sergentomyia africana were the most abundant species collected with 44.71%; 22.73%; 16.03% and 11.17%, respectively. Sergentomyia schwetzi and Sergentomyia dubia, the two species involved in the transmission of canine leishmaniasis, were found in five and four study sites respectively. According to our results, the sandfly fauna of the two geoclimatic zones of Chad is comprised of 13 species. Our data showed that, unlike P. orientalis which was not found, P. duboscqi is present in four of the five sites surveyed. Therefore, these areas are at risk and remain potential foci of cutaneous leishmaniasis. However, the need for further studies such as vector species detection, their seasonal fluctuations and their vector competence.